Tendencies Tendencies in the artistic process of creation in the plastic arts - Monteiro, Ilda (2023)
The present study, trends in the artistic creation process in the plastic arts, intends to transmit the knowledge of the theme, with specific and diversified characteristics that complement each other. In pictorial creation, the artist's action modifies the work in several phases, which end with questions, which in turn, respond to the creator's experience. In the area of visual arts, creative procedures are also related to the historical moment, social, cultural and technological aspects in which the artist is inserted. The main objective of the study is the analysis of the techniques and the results in the creative process, based on the artist's production, which had a constructive and expressive role and conditioned the aesthetic / plastic result of the work, similar to any other technology used for particular artistic object. This work presents methods and techniques of the trends verified from the artist's exploration, which questions the entire creative process of the work. The Duchampian ready-made emerges as a realization, re-evaluating the role of the artist and the way he interacts with the artistic object, with the institutions and with the specialized public against the contemporary art.